In Vitro Selection of Four Soybean Genotypes using PEG for Drought Tolerance - Saepudin, Adam; Khumaida, Nurul; Sopandie, Didy; Ardie,; Sintho Wahyuning (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2017)
The use of somatic embryo for in vitro selection program is very useful since the selected traits will be inherited in the progeny. This study was aimed to obtain somaclonal variants for drought tolerances of soybean genotypes from in vitro selection using polyethylene glycol (PEG). The experiments were set up in two factors with completely randomize design and each treatment was replicated ten times. Four soybean genotypes (Tanggamus, Anjasmoro, Yellow Biloxi, CG-22-10, and SP-10-4) were used in this study as first factor experiment. In vitro selection was in embryogenic callus level using media containing PEG (0, 5, 10, 15, and 20%) as second factor experiment was done to all genotypes. The results showed that after 3 months in the selection medium, SP-10-4 and Tanggamus genotypes showed higher percentage of fresh callus (surviving callus) and number of embryogenic callus, compared to Anjasmoro and Yellow biloxi. In contrast, CG-22-10 had the lowest number of fresh callus and number of embryogenic callus compared to other genotypes. PEG in high concentration decreased the percentage of fresh callus and number of embryogenic callus in all genotypes. Tanggamus was the only genotype that survived until cotyledonary-stage embryos after transferring in MS0 regeneration medium. Seven Tanggamus somatic embryos from PEG selection succesfully germinated and regenerated into plantlet as drought-tolerant somaclone candidates. Keywords: abiotic stress, embryogenic callus, Glycine max, somaclone